1993
DOI: 10.1002/j.2164-4683.1993.tb00132.x
|View full text |Cite
|
Sign up to set email alerts
|

Academic Self‐Concept of University Students: Implications for Counseling

Abstract: This article discusses academic self-concept for university students and its importance in conceptualization of, and program design for, higher education students. This was done by reviewing the relevant literature and examining the academic self-concept of 133 undergraduate students at a public supported land grant university in the West.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
(7 reference statements)
0
4
0
Order By: Relevance
“…ABS profile development is now overtly considered to be part of the academic staff role (Harrison et al . 1993).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ABS profile development is now overtly considered to be part of the academic staff role (Harrison et al . 1993).…”
Section: Discussionmentioning
confidence: 99%
“…ABS profile development is now overtly considered to be part of the academic staff role (Harrison et al 1993). While heeding Wankowski's (1991) warning that a student's perception of themselves as a learner may be threatened 'by the very system of tuition which was designed to make them independent learners' (p. 63), the use of self-and peer-evaluation formats must be considered together with the feasibility and means for offering assessment choice (Baird & White 1982;Cassidy & Eachus 2000).…”
Section: Possible Curriculum Developmentmentioning
confidence: 99%
“…An ABS profiles a learner's psychological approach to learning (Cassidy & Eachus 2000), their beliefs about their place and role within the academic environment. Harrison et al . (1993) suggested that academic beliefs can affect learners’ lives as deeply as their actual capabilities because beliefs influence the choices students make when formulating and accomplishing their learning objectives for example (p. 70).…”
Section: Introductionmentioning
confidence: 99%
“…ABS profiles commonly describe the following variables that reflect different aspects of the learner's perceptions. Academic self‐concept (ASC) refers to the learner's perceptions of their general academic ability (Harrison et al . 1993, p. 70) and is strongly influenced by past education and the student's perception and interpretation of it.…”
Section: Introductionmentioning
confidence: 99%